CHARACTERISTICS OF MIDGUT AMAYLASE IN BOMBYX MORI L. : A COMPARATIVE ANALYSIS IN MULTIVOLTINE RACES, PURE MYSORE AND KOLAR GOLD - MUNIV, Y.S.; CHAVAN, J.A.; PAWAR, N.T.; ALAND, S.R.; BHAWANE, G. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Assays of midgut amylase activity in two different multivoltine races i.e. Pure Mysore and crossbreed Kolar gold larvae of Bombyx mori were arranged to make the comparisons in their characterization. Optimum pH 9.2 and optimum temperature 60°C was recorded for Pure Mysore and for Kolar gold registered an optimum pH 8.8 at the temperature optima is same as in Pure Mysore. The linear period of enzyme activity was found at 10 minutes in both the races under study and Km values recorded 2.0% and 0.286% in Pure Mysore and Kolar gold respectively. The 50% inhibition at higher temperature (70°C) was found at 3 minutes in both the races. The specific activity of Pure Mysore was 34.56 ug glucose/ug protein/h, while that of Kolar gold was 86.41g glucose/ Lug protein/h.